2009
DOI: 10.1097/rhu.0b013e3181bb9865
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Hypoparathyroidism Mimicking Diffuse Idiopathic Skeletal Hyperostosis

Abstract: Idiopathic hypoparathyroidism is an uncommon disease caused by insufficient secretion of parathyroid hormone. Idiopathic hypoparathyroidism may cause various musculoskeletal findings, including diffuse ligamentous and entheseal ossifications. Diffuse idiopathic skeletal hyperostosis is a disorder of the elderly characterized by ossification of the anterior longitudinal ligament of the spine and various extraspinal ligaments. We present a 50-year-old man with idiopathic hypoparathyroidism who had been diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
(7 reference statements)
0
14
0
3
Order By: Relevance
“…Ankilozan spondilit tanısı sakroiliitin olmaması ile dışlanabilir (1). DISH, 50 yaşından önce nadir görülen, anterior longitudinal ligament ve çeşitli extraspinal ligamentlerin kalsifikasyonu ile karakterize bir kas iskelet hastalığıdır (12,13). Spinal osteofitler ve anterior longitudinal ligamentin kalsifikasyonu gibi tipik radyolojik değişiklikler ile kolayca tanısı konur (13).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ankilozan spondilit tanısı sakroiliitin olmaması ile dışlanabilir (1). DISH, 50 yaşından önce nadir görülen, anterior longitudinal ligament ve çeşitli extraspinal ligamentlerin kalsifikasyonu ile karakterize bir kas iskelet hastalığıdır (12,13). Spinal osteofitler ve anterior longitudinal ligamentin kalsifikasyonu gibi tipik radyolojik değişiklikler ile kolayca tanısı konur (13).…”
Section: Discussionunclassified
“…DISH, 50 yaşından önce nadir görülen, anterior longitudinal ligament ve çeşitli extraspinal ligamentlerin kalsifikasyonu ile karakterize bir kas iskelet hastalığıdır (12,13). Spinal osteofitler ve anterior longitudinal ligamentin kalsifikasyonu gibi tipik radyolojik değişiklikler ile kolayca tanısı konur (13). Bazı yazarlar hipoparatiroidizmdeki ligament kalsifikasyonunun ektopik kemikleşmeden ziyade metastatik ya da distrofik kalsifikasyon olduğuna inanırlar (14).…”
Section: Discussionunclassified
“…Sakroiliak eklemler korunmuştur. Genelde diyabet, hipotiroidi gibi altta yatan bir hastalık vardır (6,9).…”
Section: Introductionunclassified
“…7 Radiologically, spinal abnormalities include extensive bridging osteophytes and ossification of spinal ligaments, predominantly anterior and posterior longitudinal, interspinous, and supraspinous ligaments; these closely resemble ankylosing spondylitis(AS) and diffuse idiopathic skeletal hyperostosis (DISH). 8,9,10 Extraspinal abnormalities can be seen involving the pelvis and appendicular skeleton. The pelvis reveals ossification of sacrospinous, sacrotuberous, and iliolumbar ligaments, and ossification at the lateral margin of the acetabulum.…”
mentioning
confidence: 99%
“…Enthesopathic changes appear at various sites such as the lesser and greater trochanter, the iliac crest, and along the ischial tuberosities . 8,10,11 Kajitani TR et al reported that a 40-year-old man was referred to the Rheumatology Outpatient Clinic with a fifteen-year history of progressive inflammatory back and neck pain and prolonged morning stiffness. The patient fulfilled the modified New York criteria for ankylosing spondylitis.…”
mentioning
confidence: 99%